Perancangan Miniatur Conveyor Berbasis Mikrokontroller Dengan Penggunaan Barcode GM66 Dan Pengaruh Kinerja Servo - Samuel Tegar Eka Putra; Putri, Fenoria; Almadora Anwar Sani (MACHINERY Jurnal Teknologi Terapan, 2024)
In industrial life, one of the efficient personnel of transporting goods is a conveyor that is needed in industry, such as currently sorting goods to be delivered to each city and province. The target position is placed in the barcode sensor room where there is an infrared proximity sensor, then the material is then spilled to the conveyor head. Analysis of the results is carried out by reading information from the data obtained and the same literature, so that the research can run well. Through experiments it can be known that the final time of the specimen with parameter conditions: weight variation 100.gr 170 gr, 200 gr, 220 gr, 240 gr at a speed of 20 rpm data average efficient time 53.92 seconds, 40 rpm data average efficient time 26.25 seconds, 60 rpm data average efficient time 20.19 seconds and 80 rpm data average efficient time 18.87 seconds that there is a significant difference in the results of the final time of the specimen. The results of the linear regression method show the relationship between the specimen end time value and the positive specimen distance between the y equation 0.3211x – 21.138 in other words, the lower the specimen end time value the mean time will increase, Thus, it can be used as a reference to determine the specimen end time value.